(untitled) (Jurnal Geomine, 2015)
Nickel laterite deposits modeling was conducted to provide an overwiew of the subsurface that would define the company’s policy is the first step in mining activities the aim is to know the block model Ni who have economical levels and amount of reserves at the mine’s above the cut of grade Ni 1.5%. This research utilize estimation method inverse distance weighting with help surpac’s software. The datas that taken on field are grade, position coordinat, mount of drilling, and elevation. Result report reserve is taken for cut of grade 1.5% are 1.251.121 tons.